Kehidupan Akhirat Perspektif al-Ghazali - Hanafi Hanafi (Refleksi: Jurnal Kajian Agama dan Filsafat, 2007)
The belief in an afterlife has been held by nearly all followers of religions and belief systems since ancient times, long before the advent of Islam, up to the present day. Within the Islamic community, differences in understanding the hereafter arise due to variations in interpreting the Qur’anic verses that are somewhat ambiguous (mujmal). Al-Ghazali, in elucidating the teachings about the afterlife, consistently refers to his opinions based on Qur’anic verses and the sayings of the Prophet. In his elaboration, it can be observed that he follows the flow of information from the Qur’an and the Prophet’s sayings. This means that in his explanations, he often clarifies the meanings contained in the Qur’anic verses and relevant sayings of the Prophet, either literally or figuratively.